GAYA BERTUTUR NARATIF DALAM PENULISAN NASKAH FILM DOKUMENTER "TUNGGANGAN SANG PANGERAN" - Ahmad Fadlan (2024)
The documentary film entitled "The Prince's Ride" is a film with the theme of the Empty Horse culture originating from Cianjur, West Java. The Empty Horse culture was once prohibited from being held, therefore this film will discuss the conflict between practitioners of the Empty Horse culture and the Cianjur MUI because the Cianjur MUI issued a haram fatwa regarding the Empty Horse. This film will discuss the facts behind the MUI issuing a haram fatwa against the Empty Horse culture. Scriptwriters in documentary films have an important role, including developing an idea and theme into a film treatment which then becomes a story concept and film scenario. This observational documentary film with a narrative style about the Empty Horse Culture was made after conducting data research and field research, then as a result of this research a film script was created which was conceptualized in a structured manner using a three-act structure. This film was made to provide information regarding the Empty Horse culture, which is the original culture of Cianjur which has a history of Cianjur's independence from Mataram and become an example of conflict resolution if something similar happens in other areas